Duration of oral anticoagulation in first-episode idiopathic deep vein thrombosis: A Markov decision analysis. - Forgie, Melissa Anne. (University of Ottawa (Canada), 2001)
Deep venous thrombosis (DVT) of the lower extremity is a serious illness with an estimated incidence of 1 per 1000 persons per year. Objectives. To compare the lifetime risks and benefits of three months, six months, twelve months, two years, and lifelong anticoagulation for first episode idiopathic DVT. Secondary objectives were to assess quality of life for patients on warfarin therapy for DVT and for patients with post-thrombosic syndrome. A third objective was to determine if quality of life for these two health states differed between patients and healthy volunteers. Methods. Decision analysis with a Markov model was used to simulate patients with first episode idiopathic DVT who would be treated with durations of therapy ranging from three months to lifelong. The probabilities of clinical events were extracted from a systematic review of the literature on duration of therapy for DVT as well as rates of bleeding secondary to anticoagulant therapy and rates of developing post-thrombotic syndrome. Utilities for each of the associated health outcomes were elicited from patients and healthy volunteers using a computerized interview. (Abstract shortened by UMI.)
Keywords: Health Sciences, Medicine and Surgery.